4
$\begingroup$

Is there a closed form for

$$\sum _{j=0}^{\infty } -\frac{\zeta (-j)}{\Gamma (j)}$$

where $\zeta (-j)$ Zeta function and $\Gamma (j)$ Gamma function.

I tried everything, but I still can not solve it. Any Ideas?

$\endgroup$
  • $\begingroup$ I have tried with math software and it can't either. What makes you think that it has a closed form? First digits: $0.07932640579$ $\endgroup$ – ajotatxe Feb 7 '17 at 15:07
  • $\begingroup$ Just a point of interest, but you can replace the Gamma function and zeta function with the factorial and Bernoulli numbers respectively. $\endgroup$ – Simply Beautiful Art Feb 7 '17 at 15:07
  • $\begingroup$ It's interesting that the three answers so far, which give the same value, have such different appearances. $$1-\frac{1}{2\cosh1-2}$$ $$1-\frac{e}{(1-e)^2}$$ $$1-\frac14\operatorname{csch}^2\left(\frac12\right)$$ $\endgroup$ – robjohn Oct 29 '18 at 5:59
2
$\begingroup$

The reflection formula for the Riemann zeta function gives $$ \begin{align} \zeta(-k) %&=\zeta(k+1)\frac{\Gamma\!\left(\frac{k+1}2\right)}{\pi^{\frac{k+1}2}}\frac{\pi^{-\frac{k}2}}{\Gamma\!\left(-\frac{k}2\right)}\frac{\Gamma\!\left(1+\frac{k}2\right)}{\Gamma\!\left(1+\frac{k}2\right)}\\ %&=\zeta(k+1)\frac{\Gamma\!\left(\frac{k+1}2\right)\Gamma\!\left(\frac{k+2}2\right)}{\pi^{\frac{2k+3}2}}\sin(-k\pi/2)\\ &=\zeta(k+1)\frac{\Gamma(k+1)}{2^k\pi^{k+1}}\sin(-k\pi/2)\tag1 \end{align} $$ If $k$ is an even integer, $\sin(-k\pi/2)=0$. This matches the zeroes of the zeta function at the negative even integers. Let $k=2j-1$. $$ \zeta(1-2j) =(-1)^j\frac{\zeta(2j)}{\pi^{2j}}\frac{(2j-1)!}{2^{2j-1}}\tag2 $$ Therefore, $$ \begin{align} -\sum_{j=1}^\infty\frac{\zeta(1-2j)}{\Gamma(2j-1)} &=\sum_{j=1}^\infty(-1)^{j-1}\frac{\zeta(2j)}{\pi^{2j}}\frac{2j-1}{2^{2j-1}}\\ &=\sum_{k=1}^\infty\sum_{j=1}^\infty(-1)^{j-1}\frac{\color{#C00}{4j}-\color{#090}{2}}{(2k\pi)^{2j}}\\ &=\sum_{k=1}^\infty\left(\color{#C00}{4\frac{4k^2\pi^2}{\left(4k^2\pi^2+1\right)^2}}-\color{#090}{2\frac1{4k^2\pi^2+1}}\right)\\ &=\sum_{k=1}^\infty\left(2\frac1{4k^2\pi^2+1}-4\frac1{\left(4k^2\pi^2+1\right)^2}\right)\tag3 \end{align} $$ Using the formula from this answer $$ \sum_{k=1}^\infty\frac1{k^2+x^2} =\frac{\pi x\coth(\pi x)-1}{2x^2}\tag4 $$ and its derivative times $-\frac1{2x}$ $$ \sum_{k=1}^\infty\frac1{\left(k^2+x^2\right)^2} =\frac{\pi^2x^2\operatorname{csch}^2(\pi x)+\pi x\coth(\pi x)-2}{4x^4}\tag5 $$ we get $$ \sum_{k=1}^\infty\frac1{4k^2\pi^2+1} =\frac{\frac12\coth\left(\frac12\right)-1}{2}\tag6 $$ and $$ \sum_{k=1}^\infty\frac1{\left(4k^2\pi^2+1\right)^2} =\frac{\frac14\operatorname{csch}^2\left(\frac12\right)+\frac12\coth\left(\frac12\right)-2}{4}\tag7 $$ Applying $(6)$ and $(7)$ to $(3)$ yields $$ \bbox[5px,border:2px solid #C0A000]{-\sum_{k=1}^\infty\frac{\zeta(-k)}{\Gamma(k)}=1-\frac14\operatorname{csch}^2\left(\frac12\right)}\tag8 $$

$\endgroup$
6
$\begingroup$

Reflection formula for $\zeta(s)$ transforms the sum into $\sum_{n=1}^{\infty}\left(2\pi i\right)^{-2n}\left(2-4n\right)\zeta\left(2n\right)$. The latter can be computed by differentiating the well-known generating function $\sum_{n=0}^{\infty}\zeta\left(2n\right)z^{2n}=-\frac{\pi z\cot \pi z}{2}$, with the result $$1-\frac{1}{2\cosh1-2}.$$

$\endgroup$
  • 1
    $\begingroup$ ...you skipped a few steps there sir... $\endgroup$ – Simply Beautiful Art Feb 7 '17 at 15:17
  • $\begingroup$ (It's an awful lot of steps to not include in the answer) $\endgroup$ – Simply Beautiful Art Feb 7 '17 at 15:24
3
$\begingroup$

Using this identity:

$$\sum _{j=0}^{\infty } -\frac{x^j \zeta (-j)}{\Gamma (1+j-n)}=\frac{(-1)^{1+n} \Gamma (1+n)}{x}+(-1)^{1+2 n} x^n \text{Li}_{-n}\left(e^x\right)$$ $ n\geq 1$

where:$\text{Li}_n(x)$ is polylogarithm function.

for $x=1$, and $n=1$

$$\sum _{j=0}^{\infty } -\frac{\zeta (-j)}{\Gamma (j)}=1-\frac{e}{(1-e)^2}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.